The Epistemology of Sufi Healing in Miftāḥ al-Ṣudūr by Pangersa Abah Anom - Teten Jalaludin Hayat; Nasihun Amin; Nizar Nizar (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
The global rise of mental health issues has encouraged the search for therapeutic models that integrate spiritual and psychological dimensions. Sufism provides a rich foundation for inner healing, yet its epistemological basis is still underexplored. This study examines the epistemology of Sufi healing in Miftāḥ al-Ṣudūr [The Key of Hearts] by Pangersa Abah Anom, employing a descriptive qualitative method and the Miles and Huberman analysis model. Classical Sufi concepts like purification, emptying, and filtering of the self, combined with psychological and neuroscientific insights, form a holistic framework for self-healing. Dhikr and spiritual heart-to-heart transmission are mechanisms for inner purification, emotional regulation, and neuroplasticity. Sufi healing presents an interdisciplinary paradigm relevant to the mental health discourse; however, it is limited to textual analysis and lacks empirical field data. Future studies should incorporate ethnographic and clinical approaches involving active Sufi practitioners. Contribution: This study establishes an epistemological framework for Sufi healing by integrating classical Sufi concepts with psychological and neuroscientific insights. It introduces a new perspective on healing through epistemological awareness of mental impurity and mind-wandering.